Diterpene synthases of the biosynthetic system of medicinally active diterpenoids in Marrubium vulgare. (23rd July 2014) - Zerbe, Philipp; Chiang, Angela; Dullat, Harpreet; O'Neil‐Johnson, Mark; Starks, Courtney; Hamberger, Björn; Bohlmann, Jörg
Summary Marrubium vulgare (Lamiaceae) is a medicinal plant whose major bioactive compounds, marrubiin and other labdane–related furanoid diterpenoids, have potential applications as anti–diabetics, analgesics or vasorelaxants. Metabolite and transcriptome profiling of M. vulgare leaves identified five different candidate diterpene synthases (diTPSs) of the TPS–c and TPS–e/f clades. We describe the in vitro and in vivo functional characterization of the M. vulgare diTPS family. In addition to MvEKS ent–kaurene synthase of general metabolism, we identified three diTPSs of specialized metabolism: MvCPS3 (+)‐copalyl diphosphate synthase, and the functional diTPS pair MvCPS1 and MvELS. In a sequential reaction, MvCPS1 and MvELS produce a unique oxygenated diterpene scaffold 9, 13‐epoxy‐labd‐14‐ene en route to marrubiin and an array of related compounds. In contrast with previously known diTPSs that introduce a hydroxyl group at carbon C–8 of the labdane backbone, the MvCPS1‐catalyzed reaction proceeds via oxygenation of an intermediate carbocation at C–9, yielding the bicyclic peregrinol diphosphate. MvELS belongs to a subgroup of the diTPS TPS–e/f clade with unusual βα–domain architecture. MvELS is active in vitro and in vivo with three different prenyl diphosphate substrates forming the marrubiin precursor 9, 13‐epoxy‐labd‐14‐ene, as identified by nuclear magnetic resonance (NMR) analysis, manoyl oxide and miltiradiene. MvELS fills a central position in the biosynthetic system that forms the foundation for the diverse repertoire of Marrubium diterpenoids. Co‐expression of MvCPS1 and MvELS in engineered E. coli and Nicotiana benthamiana offers opportunities for producing precursors for an array of biologically active diterpenoids.